Formation of carbon-added anatase-rich TiO2 layers on titanium and their antibacterial properties in visible light. Issue 2 (February 2021) - Ueda, Takatoshi; Sato, Naoki; Koizumi, Ryusuke; Ueda, Kyosuke; Ito, Koyu; Ogasawara, Kouetsu; Narushima, Takayuki
Graphical abstract: Highlights: Carbon-added anatase-rich TiO2 layers were formed via two-step thermal oxidation. TiO2 layers showed antibacterial properties in visible light. TiO2 layers possessed excellent bonding strength: more than 80 MPa. Abstract: Objective: To avoid risk of infections associated with dental implants, thermal oxidation processes for practical dental Ti alloys were studied for both high bonding strength and antibacterial properties in visible light. Methods: Two-step thermal oxidation, comprising carburization (first step of treatment: in Ar-1%CO gas) and subsequent oxidation (second step of treatment: in air), was conducted on commercially pure (CP) Ti, Ti-6Al-4V (Ti64), and Ti-6Al-7Nb (Ti67) alloys to form TiO2 layers. Their bonding strengths and antibacterial properties against Escherichia coli ( E. coli ) in visible light (λ ≥ 400 nm) were evaluated. Results: TiO2 layers formed on each metal were composed of anatase and/or rutile. Anatase fraction and carbon concentration in the layers decreased with increasing temperature in the second step of treatment. Antibacterial properties of the TiO2 layers were dependent on the temperature in the second step of treatment. An approximate antibacterial activity value of 2 (killing ∼99% bacteria) was obtained when the temperatures in the second step of treatment were 673 and 773 K for CP Ti, 773 K for Ti64, and 773 and 873 K for Ti67. It was found that the TiO2 layer must contain carbon and be anatase-rich to exhibit excellent antibacterial properties. Bonding strength between the substrate and TiO2 layers formed at 773 K in the second step of treatment exceeded 80 MPa and was independent of substrate type. Significance: TiO2 layers, possessing both high bonding strength and excellent antibacterial properties, were successfully formed on practical dental Ti alloys via two-step thermal oxidation.